Empowerment from a "student as customer" perspective: Literature review and development of a framework in the context of higher education - Holger Schmidt; Carsten Baumgarth (PraxisWISSEN Marketing, 2017)
Following an intense literature research, and including results from a qualitative study with 24 graduate and post-graduate students from 14 different universities, this paper systematically discusses the topic of student empowerment within the context of higher education. The underlying perspective is that of students as customers. The article presents a simple and robust framework, which includes eight antecedents of student empowerment, the construct itself and potential outcomes for students, lecturers and institutions, and concludes with a proposal for further research within at least four distinctive areas. – – Aufbauend auf einer intensiven Literaturrecherche und einer qualitativen Studie unter 24 Studierenden von 14 verschiedenen Hochschulen diskutiert der vorliegende Beitrag das Thema der Stärkung und Aktivierung von Studierenden im Kontext der Hochschullehre. Hierbei wird eine Perspektive eingenommen, die den Studierenden als Kunden betrachtet. Im Zentrum der Ausarbeitung steht ein einfacher, aber robuster Bezugsrahmen mit acht Bedingungsfaktoren, dem Konstrukt selbst sowie möglichen positiven und negativen Auswirkungen für Studierende, Lehrende und die beteiligten Institutionen. Der Beitrag schließt mit einem Vorschlag für vier Forschungsfelder, die in diesem Kontext besondere Relevanz besitzen.
Keywords: 650; Empowerment; co-creation; student empowerment; antecedents; outcomes; higher education